Hybrid Sliding Mode Control with Gain Scheduling PID Controller for Water Tank System - Ghazali, Anith; Ab. Aziz, Nor Azlina; Wan Ismail, Wan Zakiah (International Journal of Integrated Engineering, 2024)
Water storage tank is important in many industries. A tank’s water level must be kept at a particular desired level in order for the process to run as designed in manufacturing industry, efficient farming management in agriculture sector and many other reasons. An important issue of water level management in storage tanks is the control issue in closed-loop. The proportional integral derivative (PID) controllers are popularly applied for controlling liquid level. The limitation of PID controllers is that they are feedback-type controllers, where control action is only taken when the output is affected by error. However, conventional PID controllers are unable to effectively maintain liquid level, so the need for performance improvement in the current liquid level regulators is crucial. This research implement hybrid Sliding Mode Controller with PID tuning Gain Scheduling (SMC-GSPID) controller to improves the robustness of the system. In addition, the conventional PID has been tested using three control methods of tuning which is Ziegler Nichols, Tyreus Luyben and Cohen Coon for comparison with the proposed method. All the results are validated using Matlab Simulink. The performance is evaluated using overshoot and steady state error for each controller. Based on the simulations, the suggested approach offers superior level position tracking performance with high precision compared to other PID control method with minimum overshoot of 2.9%, zero steady state error and shortest rise time which is 1.9 sec.